Mix Design of Self Compacting Concrete Based on Ultra High Compressive Strength Flow Mortar Mix - Soca Anggoro Wulan; Iman Satyarno; Ashar Saputra (Journal of the Civil Engineering Forum, 2018)
Mix design of Self Compacting Concrete or SCC is not straight forward because many parameters control its rheological properties. The case becomes more complicated if high compressive strength is also to be achieved. Therefore simpler approach is used, that is by firstly determining the flow mortar mix which is easier to be designed even with the requirement of ultra-high compressive strength. The mix design of SCC is then determined by simply adding the coarse aggregate with a certain amount of that mortar mix. In this research the ultra-high compressive strength flow mortar was made of Type I cement, 15% of cement weight silica fume, weight ratio of cement and curve No IV sand was 1: 0.35. The water-cementious ratio was 0.22 and the amount of plasticizer was 1.3%, 1.4%, 1.5% and 1.6% of the cement weight. For the SCC, the used coefficient was taken to be 1.4, 1.6, and 1.8 of the volume of that aggregate void for mortars, the aggregate value was at the volume of the remaining count of mortar and its size was 4.8 mm - 9.6 mm. Test results show that the mortar flow ability was 170 mm, 180 mm, 220 mm and 250 mm, where the achieved compressive strength was 83.1 MPa, 96.8 MPa, 111.4 MPa, and 135.5 MPa respectively. Mortar mix with 1.6% super plasticizer was then used for making the SCC and the results show that the concrete flow were 460 mm, 580 mm and 660 mm and the compressive strength were 88.2 MPa, 100.0 MPa, and 97.9 MPa.  It can be concluded that using this simpler approach the SCC can have 580 mm flow and 100 MPa compressive strength